Influence of Obesity on the Organization of the Extracellular Matrix and Satellite Cell Functions After Combined Muscle and Thorax Trauma in C57BL/6J Mice - Gihring, Adrian; Gärtner, Fabian; Liu, Congxing; Hoenicka, Markus; Wabitsch, Martin; Knippschild, Uwe; Xu, Pengfei (Frontiers in Physiology, 2020)
Obesity has been described as a major factor of health risk in modern society. Next to intricately linked comorbidities like coronary artery disease or diabetes, an influence of obesity on regeneration after muscle injury has been described previously. However, the influence of obesity on tissue regeneration in a combined trauma, merging the more systemic influence of a blunt lung trauma and the local blunt muscle trauma, has not been investigated yet. Therefore, the aim of this study was to investigate the influence of obesity on regeneration in a mouse model that combined both muscle and thorax trauma. Using gene expression analysis, a focus was put on the structure as well as the organization of the extracellular matrix and on functional satellite cell physiology. An increased amount of debris in the lung of obese mice compared to normal weight mice up to 192 h after combined trauma based on visual assessment can be reported which is accompanied by a decreased response of Mmp2 in obese mice. Additionally, a delayed and elongated response of inhibitor genes like Timp1 has been revealed in obese mice. This elongated response to the trauma in obese mice can also be seen in plasma based on increased levels of pro-inflammatory chemo- and cytokines (IL-6, MCP-1 and IL 23) 192 hours post trauma. In addition to changes in the lung, morphological analysis of the injured extensor iliotibialis anticus of the left hind leg in lean and diet-induced obese mice revealed deposition of fat in the regenerating muscle in obese animals hindering the structure of a compact muscle. Additionally, decreased activation of satellite cells and changes in organization and build-up of the ECM could be detected, finally leading to a decreased stability of the regenerated muscle in obese mice. Both factors contribute to an attenuated response to the trauma by obese mice which is reflected by a statistically significant decrease in muscle force of obese mice compared to lean mice 192 h post trauma induction.